Anti-Diarrheal Activity Of Dodonaea Viscosa Root Extracts - V. RAJAMANICKAM,; A. RAJASEKARAN,; K. ANANDARAJAGOPAL,; D.SRIDHARAN,; K.SELVAKUMAR,; B.STEPHEN RATHINARAJ, (International Journal of Pharma and Bio Sciences, 2010)
The anti-diarrheal activity of the alcohol and aqueous extracts of the roots of Dodonaea viscosa (Sapindaceae) was investigated by castor oil induced diarrhea in mice. The parameters of this study were number of diarrheal episodes and mean weight of stool of mice. The percentage protection in extract treated animals showing diarrhea was compared with castor oil treated and loperamide treated animals. The results revealed that the alcohol and aqueous extracts significantly reduced diarrhea in mice with reduction in weight of stools.